Penggunaan Variasi Bahasa Di Media Sosial Instagram “Ridwan Kamil” - Alda Fadhilah; Erina Pratiwi (Student Scientific Creativity Journal, 2023)
This article considers how the use of Indonesian on social instagram through west Java governor @ridwankamil's account. Where this instagram is being used as one means to showcase his identity as an active politician using a mixed language between Indonesian and sundanese. The study aims to know the language used by ridwan kamil in every post he posted. The study used a method with a library study type. This library study process is also used for collecting data. Based on results and discussions, analysis of the use of language styles or variations in social media has been found in a great variety of language styles such as the use of sundanese in his posts and comments column, through his personal instagram of @ridwankamil, through his personal instagram not only uploading political content but also by interacting with his followers through the instagram so that personal messages can be faster and more accessible.